1995
DOI: 10.1002/pro.5560040309
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant immunoglobulin variable domains generated from synthetic genes provide a system for in vitro characterization of light‐chain amyloid proteins

Abstract: The primary structural features that render human monoclonal light chains amyloidogenic are presently unknown. To gain further insight into the physical and biochemical factors that result in the pathologic deposition of these proteins as amyloid fibrils, we have selected for detailed study three closely homologous protein products of the light-chain variable-region single-gene family VKIV. Two of these proteins, REC and SMA, formed amyloid fibrils in vivo. The third protein, LEN, was excreted by the patient a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
60
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(68 citation statements)
references
References 53 publications
(51 reference statements)
4
60
0
Order By: Relevance
“…Crystallization studies of other AL proteins, AL-12 and AL-103, have also shown the 40 -44 loop to be disordered. 3 Therefore, this region may be a key to amyloidogenic propensity in LC proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Crystallization studies of other AL proteins, AL-12 and AL-103, have also shown the 40 -44 loop to be disordered. 3 Therefore, this region may be a key to amyloidogenic propensity in LC proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Although other precursor proteins may be wild type or linked to a single hereditary mutation, AL is distinct in that hypervariability yields a different set of mutations in each patient. Variable domains of LCs undergo somatic hypermutation, and in the case of AL patients (2), these mutations make proteins thermodynamically destabilized compared with non-amyloidogenic proteins (3)(4)(5). Some studies have linked the destabilizing somatic mutations present in AL proteins and the propensity to form amyloid fibrils that leads to cellular and organ damage (4,6,7).…”
mentioning
confidence: 99%
“…Residue Pro-40 was of particular interest because it is highly conserved in both and isotypes. Furthermore, residue Pro-40 of the multiple myeloma LEN protein has been shown to confer stability onto several amyloid-related light chains (14). We evaluated the role of Pro-40 using the 3rJL2/YA/P40S mutant (3rJL2/C34Y/ W91A/P40S).…”
Section: Site-directed Mutagenesis Of the Protective Edges Identifiesmentioning
confidence: 99%
“…The comparison of amyloidogenic and nonamyloidogenic V L sequences has allowed other researchers to identify certain amino acid changes that destabilize the V L domain (12)(13)(14)(15)(16). The introduction of some of these mutations into nonamyloidogenic V L domains decreases their stability and increases their tendency to aggregate and form amyloid fibers in vivo (17).…”
mentioning
confidence: 99%
See 1 more Smart Citation